DIETARY HABITS, NUTRITIONAL STATUS, AND BODY COMPOSITION TOWARDS THE AGILITY OF EAST JAVA HANDBALL ATHLETES - Wahono, Keysha Azhalia; Susanto, Indra Himawan; Mustar, Yetty Septiani; Bakti, Ananda Perwira (Jurnal Sporta Saintika, 2023)
Handball is a sport that involves repetitive movements (sprinting, shooting, passing, jumping) with short breaks and the athlete must be agile and have the appropriate body composition. This study looked at the relationship between dietary habits, nutritional status, and body composition with the agility of East Java Handball athletes. The cross-sectional study was conducted on 36 East Java Handball athletes consisting of 18 male athletes and 18 female athletes selected by purposive sampling with the age of 18-23 years. Independent Sample t-test and Pearson Product Moment were performed using SPSS 25. The results showed that in East Java women's Handball athletes there was a relationship between BMI and agility (p = 0.019) and men's Handball athletes there was no relationship between BMI and agility (p = 0.162). In East Java men's and women's Handball athletes, there is no relationship between percent body fat and agility (p = 0.221 and p = 0.077). In East Java men's and women's Handball athletes, there is no relationship between energy intake and agility (p = 0.681 and p = 0.879). The conclusion is that BMI correlates with athlete agility, while Percent Body Fat and energy intake do not correlate with athlete agility.